UPAYA DINAS TENAGA KERJA KOTA PEKANBARU DALAM PERLINDUNGAN TENAGA KERJA ALIH DAYA DI KOTA PEKANBARU TAHUN 2023 - Syaputra, Andri; ', Wazni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Efforts are attempts or efforts as a form of prevention, for this reason the government strives to provide welfare and security for every citizen, both in providing rights as citizens, the right to live, and the right to fulfill economic needs. This research aims to examine the efforts made by the Pekanbaru City Manpower Office to protect workers who work below the Riau Province minimum wage in the Outsourcing system in Pekanbaru City in 2023. Thus, in the process of completing this research, the researcher used a qualitative approach with data collection techniques through interviews and documentation. Interviews were conducted with the Pekanbaru City Manpower Department, Outsourcing Companies, Companies affiliated with the outsourcing system and also with the workforce. The findings show that the Manpower Department has made several efforts to protect workers, but there are still several obstacles in its implementation. These obstacles include, among other things, understanding regulations, law enforcement, and supervision of outsourcing practices. This research provides recommendations for increasing the effectiveness of labor protection efforts, including expanding understanding of regulations, increasing coordination between relevant agencies, and increasing supervision of outsourcing practices in Pekanbaru City. Keywords: Government efforts, Manpower Department, outsourcing practices